"Footprints in the Bathroom": The Role of Spirituality in Patient Diagnosis. Issue 1 (February 2017) - Meneses, Veronica; Vanderbilt, Douglas; Barnes, Linda; Augustyn, Marilyn
Abstract : CASE: Lucy is a 12-year-old Latina whose mother brought her to the pediatric clinic for help with her anxiety symptoms, "hearing voices, " and episodes of "spacing out." Lucy did not cry at birth secondary to vocal cord paralysis and still has the tracheostomy performed at a few days of life. In addition to her neonatal intensive care unit stay, she has been hospitalized for pneumonia. Her mother says she is "sickly" and has a weak immune system due to her asthma symptoms. Lucy also experiences somatic complaints related to gastroesophageal reflux and constipation. Lucy is described as being "in another world" and must be called several times before she responds. Lucy states she is nervous "all the time" and often experiences a fast heartbeat, chest pain, and headache. Her attention and internalizing problems began at age 4 years and have worsened since she entered adolescence. When she is alone in the dark, she sees an unknown person and becomes frightened. She hears the voice of her paternal uncle telling her something will harm her mother and runs crying to "check" on her. Lucy also says she hears voices of paternal family members fighting. She has dreamed that her paternal uncle stabbed her in an alley. Lucy reports experiencing sadness and feelings of wanting to die. She has not tried to harm herself and has no plan to do this. She states that she does not know when she is awake or asleep and "hate people talking in my head." She does not report drug use. Lucy's family is bilingual, English and Spanish. Her mother works part-time as a nutritionist, and her father is a machinist. Her father receives counseling for anger management, and there have been previous unsub- stantiated child abuse reports involving Lucy and her younger brother. The maternal uncle has been involved in a gang and attempts to phone Lucy's mother, who does not wish to have contact with him. Lucy's mother expresses strong Christian religious and spiritual beliefs, including demons and spirits that may enter her home and can be cast off with prayer. Recently, the family purchased a "cuadro" (picture) at a yard sale, and Lucy's mother said this resulted in footprints in the bathroom that are disappearing with prayer, guidance from the church minister, and discarding of the "cuadro." The primary pediatrician ordered a home school program, given Lucy's frequent illnesses. She is progressing well with a special education teacher. Her recent psychological evaluation at school showed a below average nonverbal intelligence quotient, with strengths in the areas of perceptual, logical, and abstract relationships. Lucy's mother in the past has been hesitant to follow through with psychiatric evaluation because "it is up to God." In the clinic, she is pale and slender with an ethereal look. She is awake and alert with appropriate affect and mentation. Her tracheostomy is intact without any respiratory distress noted. There are no signs of drug use or active hallucinations. You are left wondering whether these voices need psychiatric management.